Emergency Care in the Occupied Palestinian Territory: A Scoping Review - Raymond Rosenbloom; Rebecca Leff (Harvard FXB Center for Health and Human Rights, 2020)
The development of robust emergency care systems as a critical platform for addressing the global burden of disease has been increasingly recognized by global health policy makers over the past decade. A human rights-based approach to securing the right to quality emergency care is also essential to respond to the structural and political determinants of poor health outcomes. In the occupied Palestinian territory, human rights violations have contributed to significant deficiencies in health and quality of health care. In this scoping review, we identify deficiencies in the management of high-risk presentations to emergency departments in the Palestinian health care system for traumatic injury, acute myocardial infarction, and stroke. We subsequently apply a human rights-based analysis to demonstrate how structural racism in the administration of the occupation has contributed to deficiencies in emergency care. Specifically, deficiencies in resource and system organization within the Palestinian emergency care system arise due to occupation-related restrictions on freedom of movement, the procurement of essential drugs and medical equipment, and the development of a national Palestinian health care system. Further research and intervention are needed to understand gaps in emergency care for Palestinians and, in turn, to improve the management of emergency medical and traumatic conditions through capacity building of a Palestinian emergency care system. Importantly, deconstruction of the structural determinants of poor health for Palestinians in the occupied territory is needed to improve public health and ensure the protection of human rights.